A Minecraft movie [videorecording (DVD)] - Bowman, Chris (Christopher A.), 1976-; Palmer, Hubbel; Widener, Neil; James, Gavin (Screenwriter); Galletta, Chris, 1981-; Schroeder, Allison; Momoa, Jason; Black, Jack, 1969-; Myers, Emma, 2002-; Brooks, Danielle; Hansen, Sebastian; Coolidge, Jennifer; et al. (Warner Bros. Entertainment Inc., 2025)
"Four misfits are suddenly pulled through a mysterious portal into the Overworld: a bizarre, cubic wonderland that thrives on imagination. To get back home, they embark on a magical quest with an unexpected expert crafter, Steve. This adventure will challenge all five to be bold and reconnect with the qualities that make each of the uniquely creative."--